Promotional effect of antimony on the selective catalytic reduction NO with NH3 over V-Sb/Ti catalyst. Issue 19 (24th August 2019) - Kwon, Dong Wook; Kim, Dong Ho; Hong, Sung Chang
ABSTRACT: The effect of antimony on the selective catalytic reduction (SCR) performance and SO2 durability of V-Sb/Ti was investigated. The physicochemical characteristics of catalyst were characterized by various techniques, including Brunauer–Emmett–Teller (BET) surface area analysis, X-ray diffraction (XRD), NH3 /SO2 -temperature programmed desorption (TPD), diffuse reflectance infrared Fourier transform spectroscopy (DRIFTs), X-ray photoelectron spectroscopy (XPS), and H2 -temperature programmed reduction (H2 -TPR). The V-Sb/Ti catalyst showed excellent activity in the range 200–300°C (compared with V/Ti), with an optimum achieved for 2 wt.% antimony. The total amount of acidic sites and NH3 adsorption characteristics did not affect the catalytic efficiency. The Sb 5+ fraction was highest for V-2.0Sb/Ti and exhibited a positive correlation with the V 4+ fraction. This phenomenon is related to the effect of synergistic between vanadium and antimony, promoting the conversion of V 5+ to V 4+ by Sb 5+ . Increasing the V 4+ fraction in V-Sb/Ti increased the catalytic activity, which was mainly attributed to enhanced catalyst re-oxidation capability due to the addition of antimony. Furthermore, the addition of antimony delayed the adsorption of SO2 onto the V-Sb/Ti catalyst surface, improving the resistance to this gas. Therefore, the addition of antimony to V/Ti improved NO x conversion and SO2 durability. GRAPHICAL ABSTRACT: